2016
DOI: 10.1126/science.aaf8178
|View full text |Cite
|
Sign up to set email alerts
|

Ionic control of sleep and wakefulness

Abstract: Brain electrical activity differs markedly between wakefulness and sleep. Concomitant shifts in the ion composition of brain extracellular fluids were thought to be a consequence rather than a cause of the sleep-wake-dependent changes in neuronal activity. On page 550 of this issue, Ding et al. (1) report the surprising observation that ionic changes in the extracellular fluid are a potent control of sleep-wake-dependent neuronal activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Here, the results of [84,97] provide encouraging help, according to which the ionic composition of interstitial fluid changes significantly during sleep, as expected. More importantly, when an artificial "sleepy" intercellular fluid is applied, the brain tissues locally go into a state physiologically similar to sleep [84].…”
Section: Ngvu As Sleep Unitsupporting
confidence: 78%
“…Here, the results of [84,97] provide encouraging help, according to which the ionic composition of interstitial fluid changes significantly during sleep, as expected. More importantly, when an artificial "sleepy" intercellular fluid is applied, the brain tissues locally go into a state physiologically similar to sleep [84].…”
Section: Ngvu As Sleep Unitsupporting
confidence: 78%
“…Such active penetration into the “atomic” details of ionic reactions leads to uprising of new cytological areas, for example, nanophysiology . The importance of ionic interactions in solutions has been highlighted in a number of recent chemical and biological problems. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The underpinnings of sleep disorders following cerebral ischemia are profoundly associated with ion interference regulation [97]. Specifically, cerebral ischemia may disrupt ion channel functions and ion equilibriums, thus perturbing sleep regulation processes [98][99][100].…”
Section: Ionsmentioning
confidence: 99%
“…Reports indicated that the activation of the G protein-gated inward rectifier K + channel (GIRK) can foster NREM sleep and solidify it [102]. By examining cerebrospinal fluid in healthy individuals during sleep, wakefulness and sleep deprivation, a study found a significant decrease in K + concentrations in sleep and sleep-deprived states compared with wakefulness [97]. Concurrently, GIRK governs the circadian excitatory rhythm of brain neurons, with the regulatory process hinging on alterations in extracellular K + concentration [103].…”
Section: Ionsmentioning
confidence: 99%